Enthymemes and Topoi in Dialogue The Use of Common Sense Reasoning in Conversation - Breitholtz, Ellen (Current Research in the Semantics / Pragmatics Interface, 2020)
In Enthymemes and Topoi in Dialogue, Ellen Breitholtz presents a novel and precise account of reasoning from an interactional perspective. The account draws on the concepts of enthymemes and topoi, originating in Aristotelian rhetoric and dialectic, and integrates these in a formal dialogue semantic account using TTR, a type theory with records. Argumentation analysis and formal approaches to reasoning often focus the logical validity of arguments on inferences made in discourse from a god's-eye perspective. In contrast, Breitholtz's account emphasises the individual perspectives of interlocutors and the function and acceptability of their reasoning in context. This provides an analysis of interactions where interlocutors have access to different topoi and therefore make different inferences. Readership: All interested in the pragmatics-rhetoric interface and in theories of meaning and coherence in dialogue and discourse.